A report on the practice in industry in fish preservation. - Lorenzo, Brenda M. (College of Fisheries, University of the Philippines in the Visayas, 1966)
Capitalizing on the theoretical aspect of studies does not mean mastery of the whole field so, practice-in-industry as a requisite before graduation have been required in the College of Fisheries, University of the Philippines. At the dagat-dagatan fisheries experimental station in Malabon, Rizal, the author approached the whole scope of fish preservation-fish handling, traditional fish products, as well as the development of new products. She reposed much on her theoretical background however, some literature for new methods of preservation and the improvements of the old one have contributed much in the various experimental procedures. The author hoped that this report would make a worthwhile contribution to the literature on fish preservation. May this work aid in cleaning up many questions and that this will influence those reading it to delve into related theory and practice.